1996
DOI: 10.1161/01.str.27.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Transcortical Diaschisis After Cortical Photothrombosis in Rat Brain

Abstract: Our results suggest that a neocortical infarction leads to hyperexcitability not only in its direct vicinity but also in the contralateral hemisphere. Such hyperexcitability may contribute to increased activation of contralateral brain areas and to functional reorganization after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(113 citation statements)
references
References 42 publications
4
104
1
4
Order By: Relevance
“…Previous studies have revealed the presence of damage in contralateral brain areas after TBI. 32,33 The direct injury on the ipsilateral hemisphere may stress remote areas through transcallosal or transhemispheric diaschisis, 34 resulting in alterations in electrical activity, cerebral blood flow, and metabolites in the contralateral hemisphere. Inflammatory processes are also known to contribute to the contralateral responses after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the presence of damage in contralateral brain areas after TBI. 32,33 The direct injury on the ipsilateral hemisphere may stress remote areas through transcallosal or transhemispheric diaschisis, 34 resulting in alterations in electrical activity, cerebral blood flow, and metabolites in the contralateral hemisphere. Inflammatory processes are also known to contribute to the contralateral responses after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mechanism, long-lasting neuronal hyperexcitability in peri-infarct cortex is observed after stroke (Domann et al, 1993;Buchkremer-Ratzmann et al, 1996;Schiene et al, 1996;Mittmann et al, 1998;Neumann-Haefelin et al, 1998Redecker et al, 2002), peaking 4 weeks after stroke and persisting for 60 d (Mittmann et al, 1998). Zepeda et al (2004) demonstrated that regional reorganization 5 weeks after photothrombosis correlates with an increase in NMDA-receptor subunit levels from 1-5 weeks after stroke, while GABA levels remain reduced.…”
Section: Models For Functional Rewiringmentioning
confidence: 99%
“…Modifications of the electrical activity (Buchkremer-Ratzmann et al, 1996;Meyer et al, 1970;Witte and Stoll, 1997), cerebral blood flow (Andrews, 1991;Dobkin et al, 1989), and/or metabolism (Andrews, 1991;Kuhl et al, 1980) have been reported at the cortical level (diaschisis), mainly within areas mirror to the lesion. In animal models of cerebral ischemia, Izumi et al (2002) recently reported a progressive edema in both hemispheres within the first few hours after MCA occlusion in rats.…”
Section: Introductionmentioning
confidence: 99%